Cooperation of Ito cells and hepatocytes in the deposition of an extracellular matrix in vitro. - Loréal, O. (1993)
Cellular and molecular mechanisms involved in the deposition of extracellular matrix components in both normal and fibrotic liver are still poorly understood. We have investigated the influence of cooperation between Ito cells and hepatocytes in matrix deposition in vitro. Immunoprecipitation of radiolabeled proteins from media of 5-day-old Ito cell primary cultures showed that these cells secreted high levels of the major basement membrane components, ie, collagen IV, laminin, and entactin/nidogen. By immunocytochemistry, precursors of basement membrane components were found intracellularly, but only scarce deposits were seen around the cells. When hepatocytes were added to 2-day-old Ito cell primary cultures, they established close contacts with Ito cells in less than 24 hours and expressed ZO-1, a tight junction-associated protein not detectable in standard hepatocyte culture. Cytochemistry analysis revealed an abundant extracellular matrix deposited over hepatocyte cords and between hepatocytes and Ito cells. Immunocytochemistry studies showed that this matrix contained laminin, fibronectin, and collagens proIII and IV. These data indicate that a high level of matrix protein synthesis by liver cells in vitro is not sufficient to induce extracellular matrix deposition, and that cell-cell interactions are strongly involved in this process. Hepatocyte/Ito cell co-culture, which may reflect the actual situation in vivo, represents a useful tool for studying liver fibrogenesis.